Fulvic Acid: an Active Food Additive or Medication? - N. S. Benderskii; O. M. Kudelina; E. V. Gantsgorn; A. V. Safronenko (Кубанский научный медицинский вестник, 2020)
This review article is devoted to the fundamental task of pharmacology, i.e. the research and discovery of novel medications that render the maximal therapeutic effect at the minimal side consequences to health. Over recent years, the world has witnessed a growing interest towards natural organic compounds on the basis of humic substances (HS), which are broadly applied in animal husbandry, agriculture and veterinary medicine due to a wide spectrum of biologically active properties. The results of chemical and biological trials demonstrate that HS have a great potential for various fields of medicine.Numerous studies have demonstrated the cardioprotective, antioxidant, antitumour, antibacterial, antiviral, antifungal, antiallergic, membranotropic, hepatoprotective and anti-inflammatory properties of HS. In addition, these substances exhibit a stimulating effect on metabolism, thus enhancing specific and non-specific organismal resistance. Published evidence suggests no toxicity of HS and no inherent teratogenic, embryotoxic, mutagenic or carcinogenic properties.Fulvic acid (FA) belongs to humic acids, a family of HS. In the present study, we review its chemical properties and biological activity from the standpoint of traditional medicine. Understanding biological properties of FA and its usage in novel drug design is a perspective avenue of research in contemporary medicine.Published sources referenced in this review are indexed in Scopus, Web of Science, MedLine, the Cochrane Library, eLIBRARY, PubMed and other relevant databases.